Fungsi Hutan Kota: Korespondensi Motivasi Berkunjung dan Kegiatan - Maulana, Riyad; Riska, Annisa Safira; Kusuma, Hanson Endra (Jurnal Lanskap Indonesia, 2021)
The high intensity of urban activities tends to make people need to do recreational activities. One of the functions of the city forest is a recreational place to release the fatigue of the city community from the high intensity of social and economic activities. This research aims to uncover the relationship between the motivation of visiting and activities carried out in city forests based on people's preferences. Research is conducted through grounded theory approach with qualitative methods that are explosive. Data collection is done through the dissemination of open-ended and close-ended online questionnaires, as well as non-random sampling. The collected text data is analyzed with content analysis. The results of the analysis of motivational correspondence visited and this activity revealed two functions of the city forest, namely interactive tourism and educational tourism. Interactive tours are visitors come with motivation of the quality of the place, the activities carried out are affective and psychomotor. While educational tourism is a visitor comes with motivational information, the activities carried out are cognitive.Keywords: city forests, activities, visiting motivations, preferences.